Reliability And Operational Performance Indicators Of Expanded Functional Capability Electromagnetic Current Converters - Anarboev Mukhiddin; Davrboeva Setora (Zien Journals, 2025)
In general, reliability refers to the ability of an object (equipment, system components) to perform its designated functions within a specified volume and time under the observed conditions while maintaining its operational state within the intervals specified in normative documents
Keywords: operational; specified; object